Peripheral Giant Cell Granuloma in Edentulous Region - Zapata-Domínguez, C.; Monzón-Lloret , M.; Schiavone-Mussano , R.; Jané-Salas, E.; Devesa-Estrugo, A.; López-López, J. (The Journal of Dentists, 2014)
The peripheral giant cell granuloma (PGCG) is a benign exophytic lesion of the oral cavity. Its etiology is unknown but is associated with a local irritative or aggressive factor. The highest incidence is observed between 40-60 years, although lesions have been reported at all ages and are most commonly associated with the female sex. The treatment consists of complete excision and subsequent pathological examination of the lesion. The aim of this paper is to present the diagnosis and treatment of a case of peripheral giant cell granuloma (PGCG). The success of the case as well as its clinical and radiographic follow-up is discussed in relation to the published literature.